The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1055/s-0035-1549153
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism—Incidence of Deep Venous Thrombosis and Pulmonary Embolism in Patients with Head and Neck Cancer: A Tertiary Care Experience in Pakistan

Abstract: Introduction Although venous thromboembolism (VTE) is seen with morbidity and mortality in various surgical specialties, scarce data are available in the head and neck surgery domain. Objective We aim to determine the incidence of VTE in patients receiving surgery for head and neck cancer. Methods Four hundred thirteen patients who underwent head and neck surgery procedures between 2005 and 2013 were reviewed retrospectively. All patients with head and neck surgery had received thromboprophylaxis (i.e., compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
12
2
Order By: Relevance
“…[41][42][43] The VTE rate in our population (3.92%) was similar to previously published studies. 4,16,[44][45][46] Though it is known that patients requiring microsurgical H&N surgery are at high risk of VTE, authors have not reached a consensus on the importance of elevated BMI in this risk spectrum. In a review of 134 patients undergoing H&N microvascular reconstruction, Thai et al 9 reported a 29% increase in the risk of VTE associated with elevated BMI in patients with H&N cancer after controlling for several factors.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] The VTE rate in our population (3.92%) was similar to previously published studies. 4,16,[44][45][46] Though it is known that patients requiring microsurgical H&N surgery are at high risk of VTE, authors have not reached a consensus on the importance of elevated BMI in this risk spectrum. In a review of 134 patients undergoing H&N microvascular reconstruction, Thai et al 9 reported a 29% increase in the risk of VTE associated with elevated BMI in patients with H&N cancer after controlling for several factors.…”
Section: Discussionmentioning
confidence: 99%
“…PE is the sudden blockage of the pulmonary artery or its branches by an embolus from the venous system or the right heart, which is characterized by dysfunction of the pulmonary circulation and respiratory system. Reported studies suggest that the incidence of this complication varies between 0.05 and 2.17% in otolaryngologic diseases [ 3 6 ]. In a recent survey in our hospital, the incidence and mortality of postoperative PE in head and neck cancers patients were 0.37 and 0.11%, respectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism (VTE), which consists of deep venous thrombosis (DVT) and its sequela pulmonary embolism (PE), are the prominent causes of mortality following surgical procedures. 1 , 2 In the United States, an estimated 350,000–900,000 people develop VTE, of whom approximately 100,000 die. In addition, 30–50% of people with lower-extremity DVT develop postthrombotic syndrome.…”
Section: Introductionmentioning
confidence: 99%